Augmented Reality Applications for Cultural Heritage Using Kinect Sensor - Afyenni, Rita; Erianda, Aldo; Wahyuni, Putri; Firosha, Ardian; Gusman, Taufik; Sumema (International Journal of Advanced Science Computing and Engineering, 2024)
There are quite a number of advantages gained from Microsoft Kinect which is a motion sensing device that also includes AR applications to aid in the preservation and promotion of cultural assets. In this work, a batik model was developed with the help of Microsoft Kinect by utilizing its core components consisting of a depth sensor, an RGB camera and a microphone array to allow motion tracking, gesture recognition, and voice command functionalities of the device.The depth sensing features of the device, in particular the structural light employed, transition to Time-of-Flight technology has improved the efficiency and applicability of the device towards AR. Kinect has the ability to create an immersive AR experience by accurately mapping virtual objects to the user’s environment, leveraging body joint tracking to create a 3D skeletal model. It is required to take into consideration the kinnect positioning technique which has importance in allowing 3D objects and models to align. Therefore, the conclusion addresses Kinect as it relates to human-computer interaction, in particular, concerning its potential to change body interaction in real time and how it sets the stage for future systems that require an active interaction across a number of fields including culture and heritage.